Penerepan Evidence- Based Nursing Mencuci Tangan Menggunakan Handwash sebagai Upaya Pencegahan Diare di TK Asuhan Ibu - Rahma Aulia; Dewi Erna Marisa; Ahmad Syarifudin (STIKES Columbia Asia Medan, 2026)
The implementation of clean and healthy living behavior, especially handwashing using handwash, is one of the important efforts in preventing diarrheal disease among preschool children. Diarrhea remains a common health problem in children due to low awareness of maintaining hand hygiene before eating and after activities. This study aimed to determine the implementation of evidence-based nursing on handwashing using handwash as an effort to prevent diarrhea at TK Asuhan Ibu. The research method used was a descriptive case study with a community nursing care approach. The subjects of this study were preschool children at TK Asuhan Ibu who had improper handwashing habits. Data were collected through interviews, observations, and documentation. The intervention was carried out through health education, demonstrations, and re-demonstrations of the six-step handwashing technique using handwash. The assessment results showed that most children did not wash their hands before eating and were unable to perform the six steps of handwashing correctly. After the intervention, there was an improvement in the children’s knowledge and ability to perform proper handwashing using handwash. The children appeared to better understand the importance of handwashing as an effort to prevent diarrhea and began to develop the habit of washing their hands before eating and after playing. Support from teachers and families also increased in encouraging clean and healthy living behaviors among children. The implementation of handwashing education using handwash was effective in improving clean and healthy living behavior and served as a preventive effort to reduce the risk of diarrhea among preschool children at TK Asuhan Ibu.